Parametric and dynamic studies of an iron-based 25-kWth coal direct chemical looping unit using sub-bituminous coal. (1st May 2015) - Bayham, Samuel; McGiveron, Omar; Tong, Andrew; Chung, Elena; Kathe, Mandar; Wang, Dawei; Zeng, Liang; Fan, Liang-Shih
Highlights: Integrated, moving bed chemical looping reactor with iron-oxide based oxygen carrier. Coal carbon conversion from 84.8% to 99.9%, thermal capacity 7.4 to 27.7 kWth, O2 demand less than 1.3%. Dynamic temperature of moving bed reducer is established and tracked during coal injection. CH4 and CO present at initial coal injection, eliminated after oxygen carrier activated. Lower coal injection had higher volatiles residence time and conversion. Abstract: The iron-based Coal-Direct Chemical Looping (CDCL) combustion process is an alternative to conventional oxy-combustion technologies, where the oxygen used for fuel conversion in the CDCL process is provided by an iron-oxide based oxygen carrier instead of an air separation unit. The iron oxide is reduced using coal in the reducer reactor, producing highly-pure CO2 in the flue gas, and the reduced iron oxide is regenerated in a separate combustor reactor using air. The CDCL process at Ohio State has been developed and demonstrated in a 25 kWth sub-pilot unit, and it is the first chemical looping demonstration unit with a circulating moving bed reactor for solid fuel conversion. To date, the CDCL sub-pilot unit at OSU has been operated for more than 680 h, with a 200-h continuous operation, providing important data on long term operability as well as parametric optimization. This paper discusses recent parametric operational experience with sub-bituminous coal as the fuel, where dynamic changes in variables were performed to observe the effects on the unit itself. Measurements included temperature, pressure, and gas concentrations from the reducer and combustor. Furthermore, effects of different variables, such as flue gas recycle ratios (enhancer gas flow rates), feed port injection, and temperature, were observed. Tests confirmed high coal conversions with high purity of CO2 achieved in the flue gas. Overall, the moving bed design of the reducer results in nearly full coal conversion with a high purity of CO2, eliminating the need for additional down-stream fuel polishing and/or separation units. The combustor gas contained lean oxygen concentrations with minute amounts of carbonaceous gases detected, indicating proper regeneration of the oxygen carrier as well as good gas sealing between the reducer and combustor.